Association analysis of polymorphisms rs12997 in ACVR1 and rs1043784 in BMP6 genes involved in bone morphogenic protein signaling pathway in primary angle-closure and pseudoexfoliation glaucoma patients of Saudi origin - Altaf A. Kondkar; Tahira Sultan; Taif A. Azad; Essam A. Osman; Faisal A. Almobarak; Saleh A. Al-Obeidan (BMC, 2020)
Abstract Background Glaucoma is a polygenic neurodegenerative disease and the second most common cause of blindness in Saudi Arabia. To test the hypothesis that genetic variants in the genes involved in the bone morphogenic protein (BMP) signaling pathway may be associated with glaucoma, we investigated the association between 3' untranslated region variants, rs12997 in ACVR1 and rs1043784 in BMP6, and primary angle-closure glaucoma (PACG) and pseudoexfoliation glaucoma (PXG). Methods In a case-control study, TaqMan® real-time PCR-based genotyping was done in 444 subjects consisting of 250 controls, 101 PACG and 95 PXG cases, and tested for genetic association with glaucoma-types and other clinical phenotypes. Results Rs12997[G] allele in ACVR1 exhibited significant 2-fold increased risk of PACG (p = 0.005) in women but not in men. Similarly, genotype analysis also showed that subjects carrying rs12997[G/G] genotype were at > 2-fold risk of PACG that remained significant after adjustment for age, sex, and Bonferroni correction in the recessive model. Furthermore, this effect was also significant in women only. In PXG, the rs12997[G/G] genotype showed a significant trend towards increased risk of the disease (OR = 2.04, 95% CI = 0.99-4.18, p = 0.049) but did not survive the Bonferroni correction. Regression analysis showed that rs12997[G/G] genotype was a significant predictor of PACG independent of age, sex, and rs1043784 genotypes. Likewise, age and rs12997[G/G] genotype showed significant effect on PXG outcome. The rs12997[A/G] genotype showed significant association with cup/disc ratio as compared to wild-type (p = 0.005) in PXG. Genotype and allele frequencies of rs1043784 in BMP6 did not show any significant association either with PACG or PXG. Conclusions Our results suggest that the polymorphism rs12997 in the ACVR1 gene involved in the BMP signaling pathway is significantly associated with PACG and PXG in a Saudi cohort. This is the first study to associate this variant/gene with PACG and PXG. However, further studies would be needed to replicate these findings in a large population-based cohort.